Temperature and holding time of instrument sterilization as an infection control of odontectomy - Meliawaty, Florence; Mangundjaja, Sunardhi; Hardjawinata, Karlina (Padjadjaran Journal of Dentistry, 2011)
Odontectomy should be performed aseptically. The goal of sterilization is the complete killing of all forms of microbial life including bacterial spores on the items being processed. Biologic monitoring provides the main guarantee of sterilization. The aim of this study was to find the interrelation of the temperature and the holding time of instrument sterilization as an infection control for the successful of lower molars odontectomy. This experimental laboratory study was conducted at the Oral Maxillofacial Surgery Department in the Hasan Sadikin General Hospital Bandung and at the Microbiology Laboratory Faculty of Dentistry, Universitas Padjadjaran, Jatinangor. The Protocol was performed in three methods of sterilization: dry heat with oven and ozone, dry heat with oven and infrared (125)C for 15 minutes), both were monitored by Bacillus atrophaeus as the biologic indicators, and autoclavization (121" C for 15 minutes) with Geobaciflus stearothermophilus as the biological monitoring, with 17 times repetition. After sterilization, all of the indicators were cultured on Nutrient Agar Plate (NAPS), and the subsequent growth was assessed. The colony forming units (CFUs) were counted by Stuart Electric Bacteria Colony Counter. Adequate positive and negative controls were used in every cycle. The results showed that after autoclavization, all spores were killed. In comparison with dry heat in the oven, there were still CFUs on the NAPs, but no colonies grow after 3 repetitions by oven and infrared. Heating in oven and ozone could only reduce the spore numbers, even after repeating 5 times. The reduction of the CFUs was greater in more repetition. According to the statistical analysis, the differences were significant. This study concluded that sterilization by oven and infrared will be achieved after 3 holding times (30-35 minutes) and dry heat with oven and ozone could only act as a germicide. In autoclavization, all of Geobacillus steorothermophilus have been killed.